Robert B. Parker's stone's throw - Parker, Robert B., 1932-2010; Lupica, Mike (Parker, Robert B., 1932-2010. Jesse Stone novels, 2021)
"Paradise is rocked by the mayor's untimely death in the latest novel starring police chief Jesse Stone"--